Longitudinal Development of Primary and Secondary Posttraumatic Growth in Aging Veterans and Their Wives: Domain‐Specific Trajectories. Issue 5 (19th October 2018) - Bachem, Rahel; Mitreuter, Saskia; Levin, Yafit; Stein, Jacob Y.; Xiao, Zhou; Solomon, Zahava
Abstract: Posttraumatic growth (PTG), the positive psychological transformations that follow traumatic events, affects both direct survivors (primary PTG) and their significant others (secondary PTG). Though primary and secondary PTG have been widely investigated in the literature, their long‐term trajectories decades after a traumatic event, especially as survivors enter older age, remain largely uninvestigated. Furthermore, it remains contested whether PTG adds up to a monolithic construct or rather consists of relatively independent components. Addressing these issues, we assessed a sample of Israeli male veterans from the 1973 Yom Kippur war ( N = 349) and their wives ( N = 156) at three time points over the course of nearly three decades. Both the veterans (primary survivors) and their wives (secondary survivors) reported PTG relating to the veterans' experiences during the war and/or captivity. Latent growth mixture modeling was conducted to identify trajectories of PTG on the five subscales of the Posttraumatic Growth Inventory. Long‐term trajectories of PTG followed heterogeneous patterns of fluctuation over time and particularly as participants entered older age. On most subscales, decreasing PTG scores were evident, a trend that was more pronounced among the primary survivors than the secondary survivors as primary and secondary PTG fluctuate considerably in the long‐term and seem to decrease as individuals enter older age. Furthermore, it would seem that PTG should not be considered a holistic concept but rather a conglomeration of positive changes. Implications of the findings are discussed within the context of limitations and potential intervening factors. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Desarrollo longitudinal del crecimiento postraumático primario y secundario en veteranos ancianos y sus esposas: Trayectorias por dominios específicas TRAYECTORIAS DE LOS DOMINIOS DE CRECIMIENTO POSTRAUMÁTICO Tanto los sobrevivientes directos como sus parejas experimentan crecimiento postraumático (PTG, por sus siglas en inglés), las transformaciones positivas que siguen a los eventos traumáticos, vía PTG primaria (sobrevivientes) y PTG secundaria (parejas). Aunque el PTG primario y secundario han sido ampliamente investigados en la literatura, sus trayectorias de largo plazo décadas después de un evento traumático, y especialmente en la medida que los sobrevivientes adquieren edad avanzada, permanecen en gran parte sin investigar. Más aún, permanece controvertido si el PTG se agrega a un constructo monolítico o más bien está constituido por componentes relativamente independientes. Para abordar estos problemas, evaluamos una muestra de hombres veteranos israelíes de la guerra de Yom Kippur de 1973 (N = 349) y sus esposas (N = 156) en 3 puntos de tiempo en el curso de casi 3 décadas. Tanto los veteranos (sobrevivientes primarios) como sus esposas (sobrevivientes secundarios) reportaron PTG en relación a las experiencias de los veteranos durante la guerra y/o cautiverio. Se realizó un modelo de mezcla del crecimiento latente para identificar las trayectorias del PTG en las cinco subescalas del Inventario de Crecimiento Postraumático. Las trayectorias de largo plazo de PTG siguieron patrones heterogéneos de fluctuación a través del tiempo y particularmente en la medida que los participantes alcanzaban avanzada edad. En la mayoría de las subescalas, la disminución de los puntajes de PTG fue evidente, una tendencia que fue más pronunciada entre los sobrevivientes primarios que entre los sobrevivientes secundarios mientras que el PTG primario y secundario fluctua considerablemente en el largo plazo y parece disminuir mientras los individuos alcanzan avanzada edad. Más aún, pareciera que PTG no debería ser considerado un concepto holístico sino un conglomerado de cambios positivos. Las implicancias de los hallazgos se discuten dentro del contexto de las limitaciones y potenciales factores intervinientes. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Longitudinal development of primary and secondary posttraumatic growth in aging veterans and their wives: Domain‐specific trajectories Traditional Chinese 標題: 年紀漸長的退役軍人和他們的妻子原級和次級創傷後成長的縱貫發展: 範疇特殊的軌跡 撮要: 直接生還者與其身邊重要的人同樣會經歷創傷後成長(PTG)。那是創傷事件後的正向心理改變, 由原級PTG(生還者)和次級PTG(身邊重要的人)組成。雖然過往的文獻已廣泛地檢視原級和次級PTG, 可是, 兩者在創傷事件數十年後, 特別是當生還者踏入老年時的長遠軌跡, 仍缺乏研究。再者, PTG到底是否形成整體構念, 還是由相對獨立的成份組成, 仍備受爭議。為了解以上問題, 本研究檢視曾參與1973年贖罪日戰爭的以色列男性退役軍人(N = 349)及他們的妻子(N = 156), 在接近30年裡分3個時點進行評估。退役軍人 (原級生還者) 和妻子 (次級生還者), 都有跟退役軍人戰爭和/或受虜經歷相關的PTG。潛在成長混合模型用以找出創傷後成長量表中5個子量表的PTG軌跡。PTG的長遠軌跡有不同的起伏模式, 特別是在樣本年紀漸長時。在大多數子量表裡, PTG分數都明顯下降, 而這趨勢在原級生還者當中更為明顯。長遠來說, 原級和次級PTG一直有顯著起伏, 並似乎因樣本年紀漸長而下降。而且, PTG似乎並非一個整體構念, 而是由一些正向改變結合而成。我們亦基於結果, 討論是次研究的限制和潛在的干擾因素。 Simplified Chinese 标题: 年纪渐长的退役军人和他们的妻子原级和次级创伤后成长的纵贯发展: 范畴特殊的轨迹 撮要: 直接生还者与其身边重要的人同样会经历创伤后成长(PTG)。那是创伤事件后的正向心理改变, 由原级PTG(生还者)和次级PTG(身边重要的人)组成。虽然过往的文献已广泛地检视原级和次级PTG, 可是, 两者在创伤事件数十年后, 特别是当生还者踏入老年时的长远轨迹, 仍缺乏研究。再者, PTG到底是否形成整体构念, 还是由相对独立的成份组成, 仍备受争议。为了解以上问题, 本研究检视曾参与1973年赎罪日战争的以色列男性退役军人(N = 349)及他们的妻子(N = 156), 在接近30年里分3个时点进行评估。退役军人 (原级生还者) 和妻子 (次级生还者), 都有跟退役军人战争和/或受虏经历相关的PTG。潜在成长混合模型用以找出创伤后成长量表中5个子量表的PTG轨迹。PTG的长远轨迹有不同的起伏模式, 特别是在样本年纪渐长时。在大多数子量表里, PTG分数都明显下降, 而这趋势在原级生还者当中更为明显。长远来说, 原级和次级PTG一直有显著起伏, 并似乎因样本年纪渐长而下降。而且, PTG似乎并非一个整体构念, 而是由一些正向改变结合而成。我们亦基于结果, 讨论是次研究的限制和潜在的干扰因素。